O gênero anúncio: uma tentativa de classificação - Rabay Neto, Alfonse (2006)
his article presents some aspects about publicity genre advertising, evidenced from a sample of 40 texts. Althoughthere is manifestation of some formal characteristics established by some authors, like Martins (1995), we believe that communicativeintention (objective) is, maybe, decisive element to characterize of reported text genre. Set off some theoretical conception alreadydefinided, about type, in broad sense, and of genre, in sense restricted of advertising. Finally it will be analysed texts (advertising)with intention (objective) of observe traces (aspects) that, in fact, characterize the text genre in question.PALAVRAS-CHAVE: gêneros; gênero publicitário; gênero anúncio.